Complete Genome Sequence of Methanolinea tarda NOBI-1(T), a Hydrogenotrophic Methanogen Isolated from Methanogenic Digester Sludge - Yamamoto, Kyosuke (American Society for Microbiology, 2014)
Here, we report a 2.0-Mb complete genome sequence of Methanolinea tarda NOBI-1(T), a methanogenic archaeon isolated from an anaerobic digested sludge. This is the first genome report of the genus Methanolinea isolate belonging to the family Methanoregulaceae, a recently proposed novel family within the order Methanomicrobiales.